?ASSESSMENT OF GOSSYPIUM HIRSUTUM F1HYBRIDS AGAINST COMMERCIAL VARI fETIESNIAB-7S AND CRIS-9 IN SAKRAND CONDITIONS - Soomro, Abdul Razaque (Biological Sciences - PJSIR, 2000)
Fourteen intraspeci fie hybrids of cotton were evaluated against commercial varieties NIAB-78 and CRIS-9 in respect of yield per plant, number of bolls per plant, boll weight, ginning outturn percent and staple length. All the hybrids yielded more than NIAB- 78 and CRIS-9 except BH-41 x CRIS-54 which yielded lower than CRrS-9. 13 hybrids produced more number of bolls per plant, 7 ginned better and all the hybrids produced heavier bolls than the commercial varieties. 10 hybrids measured longer staple length. Several hybrids have the potential to be commercial hybrids.